Study of prompt photon production in hadronic Z 0 decays - Abreu,P; Adam,W; Adye,T; Agasi,E; Ajinenko,I; Aleksan,R; Alekseev,GD; Allport,PP; Almehed,S; Alvsvaag,SJ; Amaldi,U; Amato,S; et al. (Zeitschrift Fur Physik C Particles and Fields, 1995)
From a sample of 1.5 million Z 0→qq decays collected by the DELPHI detector during 1991, 1992 and 1993, the production cross section for isolated final state photons is measured and is compared with the O(α, α s) matrix element calculations implemented in the EEPRAD and GNJETS Monte Carlo generators. The observed photon yield is used to derive the electroweak couplings of charge 2/3 (u-type) and charge 1/3 (d-type) quarks to the Z 0 boson. The measured values c 2/3=0.91 -0.36 +0.25 and c 1/3=1.62 -0.17 +0.24 are compatible with the Standard Model prediction, c 2/3=1.145 and c 1/3=1.477. © 1996 Springer-Verlag.